Purification and characterization of protocatechuate 2,3-dioxygenase from Bacillus macerans: a new extradiol catecholic dioxygenase. - Wolgel, S A (1993)
Protocatechuate 2,3-dioxygenase (2,3-PCD) from Bacillus macerans JJ1b has been purified to homogeneity for the first time. The enzyme catalyzes proximal extradiol ring cleavage of protocatechuate (PCA) with the attendant incorporation of both atoms of oxygen from O2. The holoenzyme has a mass of 143 +/- 7 kDa as determined by ultracentrifugation and other techniques. It is composed of four apparently identical subunits with M(r)s of 35,500, each containing one iron atom. Mössbauer spectroscopy of 57Fe-enriched enzyme showed that the irons are indistinguishable and are high spin (S = 2) Fe2+ in both the uncomplexed and substrate-bound enzyme. However, the quadrupole splitting, delta EQ, and isomer shift, delta, of the Mössbauer spectrum changed from delta EQ = 2.57 mm/s and delta = 1.29 mm/s to delta EQ = 2.73 mm/s and delta = 1.19 mm/s upon PCA binding to the enzyme, showing that the iron environment is altered when substrate is present. The enzyme was also found to bind variable and substoichiometric amounts of Mn2+, but this metal could be removed without loss of activity or stability. The inherently electron paramagnetic resonance (EPR)-silent Fe2+ of the enzyme reversibly bound nitric oxide to produce an EPR-active species (g = 4.11, 3.95; S = 3/2). The specific activity of the enzyme was found to be correlated with the amount of the S = 3/2 species formed, showing that activity is dependent on Fe2+. Anaerobic addition of substrates to the enzyme-nitric oxide complex significantly altered the EPR spectrum, suggesting that substrates bind to or near the iron. The enzyme was inactivated by reagents that oxidize the Fe2+, such as H2O2 and K3FE(CN)6; full activity was restored after reduction of the iron by ascorbate. Steady-state kinetic data were found to be consistent with an ordered bi-uni mechanism in which the organic substrate must add to 2,3-PCD before O2. The enzyme has the broadest substrate range of any of the well-studied catecholic dioxygenases. All substrates have vicinal hydroxyl groups on the aromatic ring except 4-NH2-3-hydroxybenzoate. This is the first substrate lacking vicinal hydroxyl groups reported for catecholic extradiol dioxygenases. 2,3-PCD is the final member of the PCA dioxygenase family to be purified. It is compared with other members of this family as well as other catecholic dioxygenases.